2023
DOI: 10.7759/cureus.33831
|View full text |Cite
|
Sign up to set email alerts
|

Paxlovid-Induced Symptomatic Bradycardia and Syncope

Abstract: Paxlovid (nirmatrelvir/ritonavir) is a game changer in the fight against COVID-19 due to its ease of administration and significant benefits of reducing progression to severe COVID-19, hospitalization, and death. Cardiac adverse events such as bradycardia and syncope are not known with this medication. We report a case of a 71-year-old patient who developed symptomatic bradycardia, syncopal episodes, and sinus pause after taking Paxlovid. Discontinuing medication and intravenous atropine helped to reverse the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…A relatively high risk of drug-drug interaction has been reported with nirmatrelvir/ritonavir [ 48 ], which is worth noticing in older adults who are often receiving various medications for comorbidities. Nirmatrelvir/ritonavir is reported to be associated with TRAEs such as nausea, diarrhea, headache, running nose, and muscle ache [ 49 ], and several more severe TRAEs of nirmatrelvir/ritonavir (bradycardia and syncope) have been observed recently [ 50 ]. Few TRAEs of azvudine were previously reported [ 22 ], mainly headache, dizziness, increased aminotransferases, nausea, and increased D dimer levels [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…A relatively high risk of drug-drug interaction has been reported with nirmatrelvir/ritonavir [ 48 ], which is worth noticing in older adults who are often receiving various medications for comorbidities. Nirmatrelvir/ritonavir is reported to be associated with TRAEs such as nausea, diarrhea, headache, running nose, and muscle ache [ 49 ], and several more severe TRAEs of nirmatrelvir/ritonavir (bradycardia and syncope) have been observed recently [ 50 ]. Few TRAEs of azvudine were previously reported [ 22 ], mainly headache, dizziness, increased aminotransferases, nausea, and increased D dimer levels [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ganipisetti et al [ 10 ] reported a case of SA induced by nirmatrelvir/ritonavir administration for COVID-19 infection, with a significant correlation observed between the occurrence of SA and the medication administered. The half-life elimination of nirmatrelvir/ritonavir is approximately 6.05 ± 1.79 hours, with a metabolism rate of 94–97% after 5 half-lives [ 10 ]. The patient we report exhibited normal liver and kidney function, suggesting the absence of any metabolic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, no serious complications occurred, and the pacemaker was removed after four days [80] . Furthermore, the potential of nirmatrelvir/ritonavir to interfere with normal sinoatrial node function has also been reported [81] .…”
Section: Safety and Tolerability Of Nirmatrelvir/ritonavirmentioning
confidence: 99%